Customer-Oriented Operational Management: Improving Consumer Experience through Service Efficiency - Wibowo, Imam (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2022)
This research aims to investigate the impact of implementing customer-oriented operational management on improving consumer experience through service efficiency. With a focus on operational efficiency in service, this research will evaluate how operational management strategies that focus on customer needs and expectations can improve service quality and increase consumer satisfaction. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Customer Oriented Operational Management (MOP) by focusing on in-depth understanding of customer needs, responsiveness to customer feedback, and the application of technology to improve operational efficiency has had a positive impact. By engaging employees in a culture of innovation and implementing solutions that are responsive to changing customer needs, organizations can create better consumer experiences. The use of technology, such as inventory management systems and customer data analysis, helps in speeding up response to customers and increasing operational efficiency. Overall, this approach brings significant benefits in increasing customer satisfaction, optimizing operational processes, and positioning the organization to remain competitive in a dynamic marketplace.